2010
DOI: 10.1017/s1751731110000467
|View full text |Cite
|
Sign up to set email alerts
|

Links between ruminants’ food preference and their welfare

Abstract: Nutrition is an important aspect of welfare, and in most recommendations for the welfare of animals adequate nutrition is a primary requirement. However, in intensive livestock production systems the decision for adequate nutrition is made based on traditional paradigms of feeding monotonous rations or plant monocultures, frequently with excesses or imbalances of nutrients relative to the individuals' physiology, which can compromise welfare. Individual ruminants can better meet their needs for nutrients and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 81 publications
(58 reference statements)
0
58
0
1
Order By: Relevance
“…Recently, introduction of straw in the rumen (Baumont et al, 2007) or distension with a balloon (Villalba et al, 2009a and2009b) were used to demonstrate that rumen fill is perceived as a negative post-ingestive signal, leading to a decreased preference for the associated forage. We could thus expect the choice of grass hay to be enhanced when it is associated with intraruminal administration of lucerne hay, and conversely the choice of lucerne hay to be decreased when associated with introduction of grass hay, due to differences in fill effect between these two hays.…”
Section: Short-term Choices: Effect Of Recent Dietary Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, introduction of straw in the rumen (Baumont et al, 2007) or distension with a balloon (Villalba et al, 2009a and2009b) were used to demonstrate that rumen fill is perceived as a negative post-ingestive signal, leading to a decreased preference for the associated forage. We could thus expect the choice of grass hay to be enhanced when it is associated with intraruminal administration of lucerne hay, and conversely the choice of lucerne hay to be decreased when associated with introduction of grass hay, due to differences in fill effect between these two hays.…”
Section: Short-term Choices: Effect Of Recent Dietary Experiencesmentioning
confidence: 99%
“…This motivation for diversity may be explained by the 'satiety hypothesis' (Provenza et al, 2007;Villalba et al, 2009a and2009b), which suggests that animals acquired transient aversions for a food just eaten as a result of sensory input and post-ingestive feedbacks (nutrients and toxins) interacting along concentration gradients. This transient change in food palatability caused animal to search for a different food and then to eat a diverse diet.…”
Section: Short-term Choices: Effect Of Recent Dietary Experiencesmentioning
confidence: 99%
“…Ginane et al (2002) reported a higher daily DM intake when a choice among two hays of different or similar quality was offered than when one of these hay types was offered alone and explained this by an increased motivation to eat when a diverse offer is available. Even though high quality feeds are preferred by the animals in a choice situation, feeds with lower quality might help to motivate intake simply by increasing the diversity on offer (Ginane et al, 2002), because monotonous diets might lead earlier to a sensory-specific satiety (Rolls, 1986) thus decreasing the motivation to eat due to the lack of feed alternatives (Villalba et al, 2010). When testing different Mediterranean woody forages offered for 6 h/d by varying the number of feeds on offer between each 5-day period, intake increased or decreased along with the number of feeds (Rogosic et al, 2006(Rogosic et al, , 2007 which was explained by the changing biochemical diversity.…”
Section: Choice Vs No-choice Situations With Low-quality Foragesmentioning
confidence: 99%
“…The feed, which provides chemicals required by an animal at a certain point in space and time, will be more preferred than other feeds. In contrast, if a feed contains compounds which cause negative effects to the organism or the ones which are not needed in that particular point (e.g., excess of nutrients), the preference for the feed will decrease (Villalba et al 2010b). On this basis, ruminants preferentially ingest feeds high in nutrients (Villalba and Provenza 1997) and low in toxins (Provenza et al 1990), but they avoid specific nutrients when needs are met (Villalba and Provenza 1999), and eat toxins when they provide desirable medicinal (e.g., antiparasitic) effects (Villalba et al 2010a).…”
Section: Postingestive Feedback In Ruminantsmentioning
confidence: 99%